2019
DOI: 10.3389/fpubh.2019.00313
|View full text |Cite
|
Sign up to set email alerts
|

University Curricula in Evidence-Informed Decision Making and Knowledge Translation: Integrating Best Practice, Innovation, and Experience for Effective Teaching and Learning

Abstract: As attention to Evidence Informed Decision Making (EIDM) and Knowledge Translation (KT) in research, policy and practice grows, so does a need for capacity enhancement in amongst evidence producers and evidence users. Recognizing that most researchers enter the professional sphere with little or no appreciation of the importance and power of EIDM, the Centre for Evidence-based Health Care at Stellenbosch University, South Africa, spearheaded the development and accreditation of a foundational course titled Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Comparison of student performance on knowledge-based questions between JiTT vs. non-JiTT courses from major assessments indicated that JiTT was helpful in student's learning of knowledge-based concepts. This is in agreement with previously reported observation that JiTT methodology effectively enhanced knowledge-based skills required for understanding of core health-care professional curricular topics (2,(6)(7)(8)(9)(10)15). Additionally, analysis of mean KR-20 values from each assessment also showed that courses with JiTT pedagogy had consistent exam performance compared to non-JiTT courses offered to the same cohorts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison of student performance on knowledge-based questions between JiTT vs. non-JiTT courses from major assessments indicated that JiTT was helpful in student's learning of knowledge-based concepts. This is in agreement with previously reported observation that JiTT methodology effectively enhanced knowledge-based skills required for understanding of core health-care professional curricular topics (2,(6)(7)(8)(9)(10)15). Additionally, analysis of mean KR-20 values from each assessment also showed that courses with JiTT pedagogy had consistent exam performance compared to non-JiTT courses offered to the same cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…JiT training tool was used to validate minimum competency of bedside nursing staff managing high-risk low-volume therapies in order to ensure patient safety (14). A recent literature report also suggested that JiT active learning of evidence-based healthcare curricula created an opportunity for students to engage with facilitators and peers, enhance knowledge-based skills, and increase their chances of reinforcing and retaining their curricular knowledge (15). It is established that active learning teaching practice benefits small class sizes to a greater extent while showing an overall gain in student performance in undergraduate science, technology, engineering, and mathematics (STEM) courses compared to a traditional lecturing approach (16).…”
Section: Introductionmentioning
confidence: 99%
“…EIDM involves processes of distilling and disseminating the best available evidence from research, practice and experience and using that evidence to inform and improve public health policy and practice [ 13 , 14 ]. Knowledge translation, knowledge transfer and translational research are EIDM concepts that are closely related to implementation science, used to refer to the processes of moving research-based evidence into policy and practice, through the synthesis, dissemination, exchange and application of knowledge to improve the health of the population [ 13 , 15 – 17 ]. Although there may be nuanced differences in their conceptualisation, these terms essentially have similar goals and practical implications for improving health outconmes [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…EIDM involves processes of distilling and disseminating the best available evidence from research, practice and experience and using that evidence to inform and improve public health policy and practice. 13 14 Knowledge translation, knowledge transfer and translational research are EIDM concepts that are closely related to implementation science, used to refer to the processes of moving research-based evidence into policy and practice, through the synthesis, dissemination, exchange and application of knowledge to improve the health of the population. 13 15–17 Although there may be nuanced differences in their conceptualisation, these terms essentially have similar goals and practical implications for improving health outconmes.…”
Section: Introductionmentioning
confidence: 99%
“…Various implementation research initiatives and efforts for evaluating and improving health programme outcomes have emerged in the African region in the last decade. 13 17 25–28 In spite of this substantial growth, implementation research uptake, effectiveness and scale-up in the region are challenged by numerous barriers. 25–27 These include inadequate research funding, limited availability and access to good quality research and paucity of contextually relevant evidence.…”
Section: Introductionmentioning
confidence: 99%